2014
DOI: 10.3109/07420528.2014.940085
|View full text |Cite
|
Sign up to set email alerts
|

Repeated psychosocial stress at night, but not day, affects the central molecular clock

Abstract: We have recently demonstrated that the outcome of repeated social defeat (SD) on behavior, physiology and immunology is more negative when applied during the dark/active phase as compared with the light/inactive phase of male C57BL/6 mice. Here, we investigated the effects of the same stress paradigm, which combines a psychosocial and novelty stressor, on the circadian clock in transgenic PERIOD2::LUCIFERASE (PER2::LUC) and wildtype (WT) mice by subjecting them to repeated SD, either in the early light phase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 65 publications
3
46
0
Order By: Relevance
“…Therefore, the circadian rhythm in peripheral clocks phase shifts from that of central clock under the regulation of the HPA axis, leading to transient uncoupling of the central and peripheral clocks (48). Following termination of the acute stress, the central clock can reset peripheral clocks to their initial phase within a few days (65, 83). hGRα-induced transcriptional activity may be influenced by phase-shifted peripheral clocks in local tissues, but the specific mechanisms remain to be elucidated (Figure 2).…”
Section: Molecular Interrelations Between the Hpa Axis And The Circadmentioning
confidence: 99%
“…Therefore, the circadian rhythm in peripheral clocks phase shifts from that of central clock under the regulation of the HPA axis, leading to transient uncoupling of the central and peripheral clocks (48). Following termination of the acute stress, the central clock can reset peripheral clocks to their initial phase within a few days (65, 83). hGRα-induced transcriptional activity may be influenced by phase-shifted peripheral clocks in local tissues, but the specific mechanisms remain to be elucidated (Figure 2).…”
Section: Molecular Interrelations Between the Hpa Axis And The Circadmentioning
confidence: 99%
“…However, the SCN clock is sometimes affected by long-term stressors [2225]. Kinoshita et al [23], for example, demonstrated that 3 h of restraint stress at Zeitgeber time (ZT)6–9 for 7 consecutive days produced elevated glycogen synthase kinase (GSK)-3β phosphorylation and blunted PER2 rhythms in the SCN of mice (ZT0 and 12 are defined as the start and end of the light period, respectively).…”
Section: Stress-induced Entrainment Of the Circadian Clockmentioning
confidence: 99%
“…Kinoshita et al [23], for example, demonstrated that 3 h of restraint stress at Zeitgeber time (ZT)6–9 for 7 consecutive days produced elevated glycogen synthase kinase (GSK)-3β phosphorylation and blunted PER2 rhythms in the SCN of mice (ZT0 and 12 are defined as the start and end of the light period, respectively). In addition, 19 days of social defeat stress during the day or night induced changes in the expression of Per2 and Cry1 in the SCN of mice [22]. Moreover, chronic (4 weeks) mild stress caused decreased amplitude of PER2 rhythms in the SCN of rats, whereas 7 days of mild stress caused no alterations [25].…”
Section: Stress-induced Entrainment Of the Circadian Clockmentioning
confidence: 99%
“…The C57BL/6N substrain was used in our previous study (Bartlang et al, 2012;Bartlang et al, 2014), whereas the C57BL/6J substrain served as an adequate congenic control group for the Per1/2 double mutants that carried this genetic background. The C57BL/6N substrain was used in our previous study (Bartlang et al, 2012;Bartlang et al, 2014), whereas the C57BL/6J substrain served as an adequate congenic control group for the Per1/2 double mutants that carried this genetic background.…”
Section: Animalsmentioning
confidence: 99%
“…Yet, exposure of rats to a novel environment or restraint stress, as psychological means to raise GC levels, resulted in stronger hypothalamic-pituitary-adrenal (HPA) axis responses at early day compared with early night. SD during the early dark phase (zeitgeber time [ZT] 13 to ZT15; social defeat dark [SDD]), but not during the early light phase (ZT1-ZT3; social defeat light [SDL]), resulted in blunted activity rhythms, flattened or shifted GC rhythms (Bartlang et al, 2012), and increased PER2 protein expression and PER2 rhythm amplitudes in the SCN (Bartlang et al, 2014). In line, we have previously shown that repeated social defeat (SD) has different effects on the central clock in the SCN and peripheral output rhythms, depending on the time of day of stressor exposure.…”
mentioning
confidence: 99%